Flexible Electronics: Biocompatible Collagen Films as Substrates for Flexible Implantable Electronics (Adv. Electron. Mater. 9/2015). (15th September 2015) - Moreno, Salvador; Baniasadi, Mahmoud; Mohammed, Shakil; Mejia, Israel; Chen, Yuanning; Quevedo‐Lopez, Manuel Angel; Kumar, Nalin; Dimitrijevich, Slobodan; Minary‐Jolandan, Majid
Abstract : Collagen is an important component of the extracellular matrix. In article number 1500154, Slobodan Dimitrijevich, Majid Minary‐Jolandan, and co‐workers demonstrate its use as a substrate for implantable flexible electronics. Scanning electron microscopy (SEM) imaging shows collagen molecules forming a transparent film onto which gold metal is deposited using electron‐beam deposition to make flexible conductive metal patterns for resistors, strain/temperature sensors, and antennas that can wirelessly power light‐emitting diodes (LEDs).